Atenção compartilhada e interação social : análises de trocas sociais de crianças com diagnóstico de transtorno do espectro autista em um programa de intervenção precoce - Corrêa, Mônica Cola Cariello Brotas (2014)
The Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by social interaction impairments and communication and the presence of stereotypes and hiper sensitivity. Join Attention (JA) is indicated as a predictor of (ASD) in the first year of the child ´s life. Joint attention is the ability to share attention with a social partner, an object and an event in a triadic relationship. The social interaction relationship and joint attention is still a subject of research. The present study aimed to analyze the impact of social interaction on the JA in early intervention program for children with ASD. Our research is organized into four parts: 1) analysis of the impact of early intervention program in JA behavior of the children involved; 2) analysis of social exchanges between the participating children and the experimenter over the six months of the early intervention program; 3) analysis of social exchanges between children and their mothers, and 4) pairing the results with personal and social characteristics of caregivers. The early intervention program was developed with 15 children aged 32-42 months and their mothers, accompanied by weekly sessions, for the period of six months. The results show improvements in standards of AC in all children monitored and new patterns of social exchanges. We conclude the importance of recognizing the uniqueness of the child with ASD, the need for family involvement, offering care and support networks that protect the child and his parents in their psychosocial needs.